Prolonged Viral Shedding in Patients with Mild to Moderate COVID-19 Disease: A Regional Perspective. (April 2021) - Hossain, Mehrab E; Lister, David; Bartolo, Caroline; Kinsella, Paul M; Knox, James; Aldrich, Rosemary; Cowan, Raquel; Commons, Robert J
Background: The risk of transmission of Coronavirus Disease 2019 (COVID-19) is increasingly understood to be greatest early after symptom onset, however, factors associated with prolonged and increased risk of transmission remain unclear. In settings where COVID-19 prevalence is low, there may be a benefit of extending the period that patients are isolated to decrease the risk of transmission. This study explored the duration of viral shedding in such a location, in patients with mild-moderate COVID-19 disease in Ballarat, Australia. Methods: Patients diagnosed with COVID-19 disease using a real-time reverse-transcriptase–polymerase-chain-reaction (RT-PCR) assay from oropharyngeal and bilateral deep nasopharyngeal sampling and managed through Ballarat Health Services between March 1 and May 1, 2020 were included. Patients were retested if they were afebrile for >72 hours, asymptomatic and >14 days since symptom onset. If positive on retesting, patients were tested every 3 to 7 days thereafter. Results: Patients underwent testing a median of 4 days (range 1-12) after initial symptom onset. Duration of symptoms ranged from 1 to 36 days. Positive tests were recorded up to a median of day 21 (range 6-38). Cycle thresholds were inversely correlated with time since symptom onset ( P  < .0001). Median time to the first negative test was 25 days (range 12-32). Two patients who had remained asymptomatic for >7 days after initial symptom onset had recrudescence of mild symptoms on day 13 and 14; both tested positive on follow-up tests at this time. Conclusions: This study demonstrates prolonged shedding of COVID-19 in patients with mild-moderate disease. It suggests that some patients with mild disease may have recrudescence of symptoms a week or more after their initial symptoms resolved.